The Effect Of Compensation, Workenvironment, And Career Development On Village Office Retention In Air Periukan District, Seluma Regency - Afriani, Sulisti; Herlin, Herlin; Diwangkara, Agustio (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The purpose of this study is to determine the influence of compensation, work environment and career development on the retention of village apparatus in the sub-district of Air Periukan, Seluma Regency simultaneously or partially. The analysis method used was quantitative using multiple linear regression analysis, the sample in this study was 60 respondents and primary data collection using questionnaires. The results of this study show that compensation has a positive and significant effect on the retention of village apparatus in the sub-district of Air Periukan, Seluma Regency, where the tcount is 4,041 > ttable is 2,003 and the significant is 0.000. The work environment has a positive effect on the retention of village apparatus in the sub-district of Air Periukan Seluma Regency, where the tcount is 2,626 > ttable is 2,003 and significant 0.011. Career development has a positive effect on the retention of village apparatus in the sub-district of Air Periukan Seluma Regency, where the tcount is 2,903 > ttable 2,003 and significant 0.005. Compensation, work environment and career development simultaneously have a positive and significant effect on the retention of village apparatus in Air Periukan District, where the number of 21.43 > the number of 2.77 and the significant number of 0.000. The results of the Adjusted R Square value determination coefficient test of 0.510 showed that compensation, work environment and career development had a positive and significant effect on village apparatus in Air Periukan District, Seluma Regency.